Palladium-Catalyzed Cycloisomerization of Carbamimidothioates - Kumazawa, Hyu; Mizoguchi, Kota; Okura, Yoshifumi; Nakada, Masahisa (Synlett, 2024)
A palladium-catalyzed cycloisomerization of carbamimidothioates with the formation of a quaternary carbon and a sulfide is described. The use of (IPr)Pd(allyl)Cl (CX21), K3PO4, and Me-C(OTBS)=NTBS in refluxing xylenes was optimal, and the methoxycarbonyl group was the most suitable substituent for the nitrogen atom of the carbamimidothioate. Phenyl and alkyl groups can be used as tethers for carbamimidothioates, and alkyl and aryl carbamimidothioates can undergo Pd-catalyzed cycloisomerization in high yields.
Keywords: carbamimidothioates; cycloisomerization; palladium catalysis; quaternary carbon; sulfides